Calbindin positive Purkinje cells in the pathology of human cerebellum occurring at the time of its development - Laure-Kamionowska, Milena; Maślińska, Danuta (Folia Neuropathologica, 2009)
Development of cerebellum continues over an extremely long period of time extending from the early embryonic phase until the first postnatal years. During an extended time of maturation the cerebellum is vulnerable to harmful agents. A group of cytoplasmic proteins that may protect cells against injury are the calcium binding proteins, among others calbindin. The distribution of this protein is not well known in cerebellar pathology, thus in the present study the localisation and appearance of calbindin expressing Purkinje cells in different pathological conditions occurring at the time of cerebellar development was examined. The investigations were carried out on human maturing cerebellar cortex (age range 30 gestational weeks - 2 years) of cases with paraneoplastic cerebellar degeneration and cerebellar neuronal migration disturbances. The Purkinje cells located in cerebellar heterotopias and dysgenesias were morphologically well developed and strongly immunostained with calbindin antibody. In paraneoplastic cerebellar degeneration the progressive decrease of calbindin content and disintegration of Purkinje cells were observed. Our results show that intrauterine harmful agents that disturb migration of the cerebellar neurons do not affect the content of calbindin in misoriented neurons and that this protein may play a role in development of Purkinje cells located in heterotopias and cerebellar dysgenesias. The progressive decrease of calbindin content in the Purkinje cells undergoing degeneration and death during paraneoplastic changes in the cerebellum also supports the hypothesis that this protein is very important component of intracellular homeostasis in cerebellar neurons.